Generalities and applications of pavement instrumentation with field conditions in Costa Rica - Wang Qiu, Sheng Qi (2025)
Pavement instrumentation under field conditions is one of the methodologies that LanammeUCR is currently applying to meet its objectives of studying and analyzing Costa Rica’s pavements with the purpose of improving their performance in the medium and long term. Pavement instrumentation is mainly used to determine the behavior a pavement shows under the effects of externally induced loads or natural phenomena, which allows a diverse range of uses: pavement structural monitoring, generation of mathematical models, development of tests for the validation of pavement designs, validation of other study methods, among others. Generally, in the field of pavement engineering, the acquired behavior corresponds to the response (stresses and strains) of the pavement, which is registered through the instrumentation used in these structures and the acquired information can be used in the applications mentioned before. This study shows the procedures and preliminary results that LanammeUCR has applied and acquired regarding the instrumentation of pavements under field conditions in Costa Rica.